THEORETICAL AND GENERAL BASIS OF EFFECTIVE ORGANIZATION OF THE PEDAGOGICAL ACTIVITY OF FUTURE TEACHERS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article examines the factors of effective organization of pedagogical activity of future primary school teachers, formation and development of professional motivation, and ways of effective implementation of professional and methodological activities of teachers. The theoretical and general aspects of the development of professional competencies and methodological preparation in the formation of professional motivation in future teachers are scientifically based.